2019
DOI: 10.1186/s12014-019-9255-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential early clinical stage colorectal cancer diagnosis using a proteomics blood test panel

Abstract: Background: One of the most significant challenges in colorectal cancer (CRC) management is the use of compliant early stage population-based diagnostic tests as adjuncts to confirmatory colonoscopy. Despite the near curative nature of early clinical stage surgical resection, mortality remains unacceptably high-as the majority of patients diagnosed by faecal haemoglobin followed by colonoscopy occur at latter stages. Additionally, current populationbased screens reliant on fecal occult blood test (FOBT) have l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 76 publications
4
60
0
Order By: Relevance
“…APOA4 is a major component of high-density lipoproteins and chylomicrons. Previous studies reported the association of aberrant APOA4 expression with colorectal cancer development in diabetic patients [25] and a reduced plasma abundance in colorectal cancer patients [26]. In our current study, the plasma level of APOA4 was significantly reduced in the PDAC-DM cases compared to the controls (CP-DM and DM).…”
Section: Discussionsupporting
confidence: 63%
“…APOA4 is a major component of high-density lipoproteins and chylomicrons. Previous studies reported the association of aberrant APOA4 expression with colorectal cancer development in diabetic patients [25] and a reduced plasma abundance in colorectal cancer patients [26]. In our current study, the plasma level of APOA4 was significantly reduced in the PDAC-DM cases compared to the controls (CP-DM and DM).…”
Section: Discussionsupporting
confidence: 63%
“…The results showed 50 proteins to be abundant in the vein draining part of the cancerous regions compared to the noncancerous sectors [158]. In another study done by Ahn et al [159] one hundred plasma samples from different stages of CRC and healthy controls were pooled to create a SWATH library. Similarly, the abundant proteins were depleted and peptides were further fractionated.…”
Section: Blood-based Proteomicsmentioning
confidence: 99%
“…Another unmet clinical need is a blood‐based test for the early detraction and staging of colorectal cancer (CRC). Ahn et al (2019) used a multidimensional purification strategy comprising high abundance protein ultradepletion (MARS‐14 and an in‐house IgY depletion column [64]), strong cation exchange (SCX), strong anion exchange (SAX), high pH, and size exclusion chromatography (SEC) followed by SWATH‐MS to reveal protein biomarkers from a cohort of 100 plasma samples (20 healthy and 20 stage I–IV CRC pooled plasmas). A total of 37 potential protein biomarkers were identified that exhibited differential expression across CRC stages compared with healthy controls.…”
Section: Toward Personalized/precision Medicinementioning
confidence: 99%